Faktor-Faktor Yang Berhubungan Dengan Kejadian Ispa Di Wilayah Kerja Puskesmas Sumarorong Kecamatan Sumarorong Kabupaten Mamasa - Arif, Muhammad Ikbal; Andara, Wilda (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
The cause of ARI is influenced by environmental conditions that do not meet health requirements which can be a source of disease transmission based on the environment, the transmission of ARI disease can be caused by a dirty environment that affects the occurrence of ARI disease.The purpose of this study was to determine the factors associated with the incidence of ARI in toddlers in the Sumarorong Health Center Working Area, Sumarorong District, Mamasa Regency. The type of research used in this study was analytical observational with a Cross Sectional approach, with a sample of 89 toddlers. Data processing was carried out using the Chi Square Test. The results showed that the data of the house cleanliness variable obtained X2hitung = 10.482 with p = 0.001 <0.05, the data of the temperature variable obtained X2hitung = 11.871 with p = 0.001 <0.05, the data of the humidity variable obtained X2hitung = 18.613 with p = 0.001 <0.05 and the data of the ventilation variable X2hitung = 13.315 with p = 0.001 <0.05 means that these four variables have a significant relationship to the incidence of ARI. The conclusion in this study is that the variables studied have a significant relationship to the incidence of ARI, namely the variables of house cleanliness, temperature, humidity and ventilation. It is expected that mothers who have toddlers should pay more attention to the cleanliness of their environment.Keywords: ARI incidence; House Cleanliness; Temperature; Humidity; Ventilation